Na fronteira da língua: um estudo sobre os processos imigratórios e o autismo na infância na cidade de Foz do Iguaçu - Bonotto, Karina Ferreira Marques (2023)
Autism Spectrum Disorder (ASD) is identified through signs, using protocols and clinical observation in motor, cognitive and/or social field. In the global context of child development and growth, when one of these development areas is delayed, efforts are made to detect what is affecting the child. Its causality is multifactorial, which leads to numerous studies on risk factors including biological genetic suscetibility, hereditary, and environmental factors. This research aimed to understand the profile of ASD in children aged 0 – 12 years old in Foz do Iguaçu/PR, as well as comprehend the immigration process of families with diagnosed children. This focus is justified since research indicates factors related to this condition, suggesting that immigrant children might be more predisposed to autism, however, this factor is neither determining nor conclusive, that is, immigrating is not a causal factor, but studying the immigration process, is a way of understanding the phenomenon in this population. Therefore, an exploratory and descriptive study with a quali-quantitative approach was conducted.. In the qualitative phase, families with immigrant members, up to the second generation, who have children with ASD were interviewed. The guiding framework for the interviews and their analysis was French discourse analysis. In the quantitative phase, data were collected using an online self-report provided to family members. The survey identified 181 children up to 12 years old diagnosed with ASD. Of these, 86 (47.5%) required level 1 support, and the same number (n=86; 47.5%) also required level 2 support . Only 76 (42%) received care from either the Unified Health System. Health and 16 (8.8%) do not carry out monitoring in either the public or private sectors. As to the qualitative analysis, 9 families participated, and the interviews were transcribed and interpreted. The following categories emerged: “Who speaks the language? Language and speech”; "Immigration"; “A Foreigner in Familiar Lands – about Identity and Belonging”; “Culture – between us and border ties”; “Autism(s) – between the diagnosis, the parents and the individual”; “Multilingualism and autism – speech acquisition for immigrant children”; and “The treatment of autistic children and the role of parents and/or primary caregivers”. Listening to immigrant families and understanding how the immigration process occurred, how these families established and built connections with the local community, the process of diagnosing ASD, and how the care network was built was fundamental for understanding their cultural belongings and identities. Therefore, it is essential to clarify that, this study did not find a correlation between immigration and autism. The research was able to explore and describe the scenario in Foz do Iguaçu, and how it serves its children with ASD.